Software developers as users : semiotic investigations in human-centered software development /: semiotic investigations in human-centered software development. ([2016]) - De Souza, Clarisse Sieckenius; Cerqueira, Renato; Afonso, Luiz Marques, 1973-; Brandão, Rafael Rossi de Mello, 1982-; Ferreira, Juliana Jansen, 1979-
No abstract available